Misconceptions and Consequences of the ‘Other’ in the Sinhala Buddhist-Muslim Relationship in Sri Lanka - Sithy Rifa Mahroof; Ahamed Sarjoon Razick (Esensia: Jurnal Ilmu-Ilmu Ushuluddin, 2023)
Sri Lanka’s plurality is reflected in its religious and ethnic diversity. In recent times, there has been polarization between the majority Sinhala Buddhists and the minority Muslim groups. The objective of this study is to identify the reasons for blaming the “other” in the relationship between the two groups and propose remedies. The study adopted a descriptive and interpretive paradigm within the qualitative approach. Secondary sources were used to examine the phenomenon under study. The theoretical framework was drawn from Said’s concepts of “self” and “other”. The dominance of the Sinhala language and the utmost position given to Buddhism has made the extremist Buddhists take supremacy over the Muslims who are perceived as a threat to their “self”. The Buddhists need to be open to accepting the “otherness” of the Muslims. The consequences of the misconceptions targeted against the Muslims act as barriers to the Buddhist- Muslim relationship in Sri Lanka. The shift in attitudes of the Buddhists is not due to their own judgment but one constructed by social media. The Muslims’ ethnoreligious identity is questioned for radicalization. Inter-religious education and inter-faith dialogue between followers of Buddhism and Islam need to be promoted as both religions command engagement with the “other” on the basis of peace, tolerance, and non-violence, regardless of the differences that may exist. Understanding the fundamental unity of humankind and their ethnoreligious plurality as the two sides of the same coin, they need to engage with and understand one another as a “Sri Lankan”.